¿Can Aristotle guide us? The ‘good life’ from the discursive ethics - López de Lizaga, José Luis (Estudios de Filosofía, 2010)
This paper examines whether it is possible to approach the Aristotelian “good life” or happiness from the conceptual framework of postkantian Ethics: Ethics of discourse. The paper states that the contemporary Ethics only admits a subjectivistic conception of “good life” and it is incompatible with a rational treatment of it, such as Aristotle pretended. Then, it is stated that the question about “good life” can still be interesting for Contemporary Ethical Theory, if it is rede ned in terms of a theory of the formal conditions that must be ful lled by an autonomous determination of the “good life”, that is to say, a determination non-distorted by self-deception or false conscience. But again, the paper argues that, for such purpose, a psychological or social theory can be more relevant than an Aristotelian ethical approach.